Pelatihan Emotional Intelligence untuk Meningkatkan Kemampuan Manajemen Konflik Pada Siswa SMA - Natasha Gandhi; Putu Hening Wedanthi; Setyani Alfinuha (Universitas Islam Tribakti Lirboyo Kediri, 2021)
The purpose of this study was to see the effectiveness of emotional intelligence training in helping subjects overcome the conflict they were experiencing. Conflict is a situation where each other conflicts with each other. In the organisation's scope, namely the Student Council, conflict refers to disagreements between people or members of the Student Council. Improper application of conflict management can lead to unsanitary working conditions. It shows the importance of the intervention given to manage conflict, especially in the Student Council, which is through emotional intelligence training. The research design used was experimental (one group pretest-posttest) with 19 subjects (15-18 years). The training consisted of six sessions and was conducted over two days. The results obtained from this study were that there was a significant increase and change in the integrating type (p = 0.027, p<0.05) and compromising (p = 0.021, p<0.05). While the other types, namely domination, avoiding, and obliging, did not experience significant changes. Through emotional intelligence training, participants will learn how to control emotions so that when faced with problems, participants can use appropriate conflict management to solve these problems.